A Look Into the Past. Serbia 1965-91, part 6: Party Plays the Oracle - Paković, Zlatko (Anрelizh, Bojan, 2003)
Late 80s in the former Yugoslavia – economic crisis, high levels of debt, inflation, unemployment. The Serbian Academy of Arts and Sciences' Memorandum, the first program committed to paper that promotes the national unity of Serbs even beyond Serbia's borders. Tendencies towards more independence grow stronger in Slovenia and Croatia, as well as in the province of Kosovo. In East Europe's last decade of communism, it is authoritarianism that carries the day in Serbia. The dogmatic wing in the League of Communists of Serbia that defeats the pro-compromise group, joins hands with opposition cultural elites.